2011
DOI: 10.1016/s1078-5884(11)60012-9
|View full text |Cite
|
Sign up to set email alerts
|

Chapter V: Diabetic Foot

Abstract: Ulcerated diabetic foot is a complex problem. Ischaemia, neuropathy and infection are the three pathological components that lead to diabetic foot complications, and they frequently occur together as an aetiologic triad. Neuropathy and ischaemia are the initiating factors, most often together as neuroischaemia, whereas infection is mostly a consequence. The role of peripheral arterial disease in diabetic foot has long been underestimated as typical ischaemic symptoms are less frequent in diabetics with ischaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 131 publications
2
172
0
20
Order By: Relevance
“…The results we observed are in agreement with the recent guidelines of the European Society for Vascular Surgery on the treatment of diabetic foot [34], which notes, ''Endovascular therapy for infrapopliteal arterial disease is gaining acceptance as a first-line revascularization method to improve ulcer healing and limb salvage.'' We also agree with the recommendation of these guidelines: ''The choice between different methods of revascularization-open, endovascular or hybrid-depends on comorbidity, severity and extension of the arterial lesions as well as the expertise of the center (Level 2c; Grade B)'' [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results we observed are in agreement with the recent guidelines of the European Society for Vascular Surgery on the treatment of diabetic foot [34], which notes, ''Endovascular therapy for infrapopliteal arterial disease is gaining acceptance as a first-line revascularization method to improve ulcer healing and limb salvage.'' We also agree with the recommendation of these guidelines: ''The choice between different methods of revascularization-open, endovascular or hybrid-depends on comorbidity, severity and extension of the arterial lesions as well as the expertise of the center (Level 2c; Grade B)'' [34].…”
Section: Discussionsupporting
confidence: 90%
“…We also agree with the recommendation of these guidelines: ''The choice between different methods of revascularization-open, endovascular or hybrid-depends on comorbidity, severity and extension of the arterial lesions as well as the expertise of the center (Level 2c; Grade B)'' [34].…”
Section: Discussionsupporting
confidence: 73%
“…Az esetek többsége döntően a perifériás verőérbetegség előrehaladott stádiumához, a kritikus végtagi keringészavarhoz köthető [1], illetve a diabeteses láb szindróma következménye [2]. Utóbbi esetben a végtagot ellátó artériák keringészavarán túl, a diabeteses neuropathia, kisérkeringési zavar, csont-és ízületi eltéré-sek, infekciók változó arányú jelenléte tehető felelőssé a végtag elvesztéséért [3,4].…”
Section: öSszefoglaló Közleményunclassified
“…If not adequately treated, these ulcers may lead to The causal pathways to diabetic foot ulceration and amputation [4,9,[11][12][13][14][15] (modified based on the work of Lepäntalo et al , reprint with permission). The tissue damages in lower extremities caused by DM result in diabetic neuropathy, whereafter the somatosensory and autonomic functions are diminished or completely lost.…”
Section: Diabetic Foot Complicationsmentioning
confidence: 99%
“…Besides, tissue structures and contents, such as thickness of the epidermis layer, determine the formation of the scattered diffuse reflection, which also accounts for changes in spectral reflection [45][46][47]. Impairments in microcirculation and macrocirculation of the diabetic foot play an important role in the development of diabetic foot ulcerations and the subsequent failure to heal [4,9,[12][13][14][15]48]. Initial studies found that reduced oxygen supply might be the main reason for the development of the tissue hypoxia and nerve dysfunction [49].…”
Section: Skin Optics -Basis For Spectroscopy As a Diagnostic Toolmentioning
confidence: 99%